Understanding Arctic oil and gas : entanglements of gender, emotions and environment - Kangasluoma, Sohvi (Helsingin yliopisto, 2023)
The Arctic imaginary is often characterized by white snow, empty vastness – and extensive natural resources. The topic of oil and gas, in the Arctic or elsewhere, is becoming increasingly important, as our planet is warming. However, while attention to the global climate crisis, alongside environmental awareness, has accelerated, the extraction of hydrocarbons is still a reality in many Arctic nations. The tentacles of the industry are widespread: besides benefitting the nation states and companies working with oil and gas, the fossil fuel production is meaningful also for the local communities, the seabed and the animals of the North. The issues of energy, fossil fuels, and climate change in the Arctic are widely discussed, researched, and debated. However, the topic is usually approached with a focus on the economic, to some extent environmental, and increasingly nationalist narratives, while the social aspects of energy production are left invisible. This dissertation focuses on notions seldomly connected to the discussion on northern hydrocarbons: gender and emotions. In order to move beyond fossil fuels and achieve a just and sustainable energy transition, we must evaluate the different dimensions embedded within fossil fuel dependency. Against this backdrop, in this work I ask; 1) How is the social world of fossil fuels constructed? 2) How does paying attention to emotions and affects help to understand resource politics in the Arctic? and 3) How is the practice of the fossil fuel industry gendered? This dissertation consists of four peer-reviewed articles and a concluding synthesis. In the articles, I look at different levels and views of the northern fossil fuel world, focusing especially on Norwegian and Russian fossil fuel spheres. My underlying approach to the topic emerges from the literature and discussions of feminist international relations, woven together with critical ideas of the Arctic. I explore a variety of material produced by the oil and gas companies operating in the Arctic, interviews ...